Amino-Termination of Silicon Carbide Nanoparticles - Szabolcs Czene; Nikoletta Jegenyes; Olga Krafcsik; Sándor Lenk; Zsolt Czigány; Gábor Bortel; Katalin Kamarás; János Rohonczy; David Beke; Adam Gali (Nanomaterials, 2023)
Silicon carbide nanoparticles (SiC NPs) are promising inorganic molecular-sized fluorescent biomarkers. It is imperative to develop methods to functionalize SiC NPs for certain biological applications. One possible route is to form amino groups on the surface, which can be readily used to attach target biomolecules. Here, we report direct amino-termination of aqueous SiC NPs. We demonstrate the applicability of the amino-terminated SiC NPs by attaching bovine serum albumin as a model for functionalization. We monitor the optical properties of the SiC NPs in this process and find that the fluorescence intensity is very sensitive to surface termination. Our finding may have implications for a few nanometers sized SiC NPs containing paramagnetic color centers with optically read electron spins.